Conversion of levulinic acid over Ag substituted LaCoO3 perovskite. (1st October 2021) - Seguel, J.; Leal, E.; Zarate, X.; Saavedra-Torres, M.; Schott, E.; Díaz de León, J.N.; Blanco, E.; Escalona, N.; Pecchi, G.; Sepúlveda, C.
Graphical abstract: Highlights: The Co 2+ surface species in the LaCoO3 perovskite favor the Levulinic acid conversion. An increase Co 3+ surface species were detected in the La1-x Agx CoO3 perovskites. A partial reduction post-reaction was confirmed by XPS in La1-x Agx CoO3 perovskites. The basic sites and Co 2+ species of La1-x Agx CoO3 favor the pentanoic acid formation. Abstract: The present work shows the application of substituted and basic perovskites as catalysts in the levulinic acid conversion. In this context, the effect of the Ag substitution on La1-x Agx CoO3 (x = 0.00, 0.05, 0.10, 0.20) catalysts is reported. The catalysts were characterized by X-ray diffraction (XRD), specific surface area (BET), temperature programed reduction (H2 -TPR), methanol-temperature-programmed reaction (CH3 OH-TPR) and X-ray photoelectron spectroscopy (XPS) and their catalytic performance was evaluated in a batch reactor at 250 °C and 50 bar of H2 . The highest catalytic activity was obtained for the non-substituted LaCoO3 perovskite attributed to a high amount of surface Co 2+ . The post-reaction XPS characterization of the La1-x Agx CoO3 (x = 0.00, 0.05, 0.10, 0.20) perovskites indicates a partially reduction during the catalysis. The silver substitution increases the perovskites stability in reducting atmosphere, being the xAg = 0.05 the largest. In the levulinic acid (LA) conversion, an increase at shorter reaction times was detected in the formation of HPA as an intermediate followed by dehydration to form GVL. The further hydrogenation step produces pentanoic acid (PA). The presence of reduced surface cobalt species and basic sites in the Ag substituted perovskites promotes the conversion of levulinic acid and selectivity to higher hydrogenation compounds, indicative of that these mixed oxides can be used successfully in hydrotreatment reactions of biomass platform molecules.